PTU-103 Characterisation of the immune profile in chronic hepatitis b patients following nucleos(t)ide discontinuation by cytof mass cytometry. (22nd June 2015) - Rivino, L; Van Den Berg, M; Gill, US; Le Bert, N; Koh, S; Hansi, NK; Newell, E; Foster, GR; Bertoletti, A; Kennedy, PTF
Abstract : Introduction: Identifying chronic Hepatitis B virus (HBV) patients in whom nucleos (t)ide analogues (NUCs) can be safely discontinued with sustained immune control is a major unmet need of current treatment strategies. Predicting the onset of biochemical relapse or hepatic flares (HF) following NUC discontinuation is currently not possible. Through the utilisation of cytometry time of flight (CyTOF), a novel mass cytometry technology, in conjunction with traditional flow cytometry tools, the aim of this study was to establish an immune profile associated with the onset of HF upon withdrawal of NUC therapy. Method: Cytokine and chemokine serum levels (IL-1β, IL-6, TNF-α, IL-10, CXCL-8, CXCL-10) were measured longitudinally using Luminex in chronic HBV patients who developed HF (n = 6) and in those who did not (n = 2) upon the discontinuation of NUCs. HBV-specific T cell responses were assessed after in vitro expansion of patient peripheral blood mononuclear cells with overlapping HBV peptide pools. An in-depth longitudinal analysis of the expression of 35 markers involved in the activation, differentiation, exhaustion and anti-viral effector function of T and NK cells was performed by CyTOF mass cytometry. Results: The analysis of HBV-specific T cells using overlapping HBV peptides, shows that in patients with biochemical relapse after therapy withdrawal, there was no detection of functional antigen-specific T cells at all time points. The onset of HFs was, however, associated with a significant increase in the serum levels of CXCL-10 and IL-10. In contrast, a chronic HBV patient that controlled viral relapse without experiencing HF displayed functional circulating HBV-specific T cells. Preliminary analyses by CyTOF also revealed significant differences in terms of the frequency and functionality of the bulk of the T and NK cell populations both longitudinally (during and after discontinuation of therapy), as well as amongst patients characterised by relapse or immune control. Conclusion: Consistent with previous studies, HFs are associated with an increase in the serum levels of CXCL10 and IL-10 while HBV-specific T cells remain undetectable in the periphery. The absence of circulating virus-specific CD8 + T cells during HFs suggests that hepatic inflammation after NUC withdrawal in chronic HBV patients is induced independent of virus-specific CD8 + T cells. CyTOF technology represents a major advance, allowing us to investigate multiple parameters, providing a unique insight into potential biomarkers associated with sustained immune control of HBV. Disclosure of interest: None Declared.